Molecular Mechanism of NLRP3 Inflammasome Activation - Jin, Chengcheng; Flavell, Richard A (Journal of clinical immunology, 2010)
The inflammasome is an intracellular multimolecular complex that controls caspase-1 activity in the innate immune system. NLRP3, a member of the NLR family of cytosolic pattern recognition receptors, along with the adaptor protein ASC, mediates caspase-1 activation via assembly of the inflammasome in response to various pathogen-derived factors as well as danger-associated molecules. The active NLRP3 inflammasome drives innate immune response towards invading pathogens and cellular damage, and regulates adaptive immune response. Here, we review identified agonists of the NLRP3 inflammasome and the molecular mechanism by which they induce NLRP3 inflammasome activation. Three signaling pathways involving potassium efflux, generation of reactive oxygen species, and cathepsin B release are discussed.